2008
DOI: 10.1037/0893-3200.22.1.144
|View full text |Cite
|
Sign up to set email alerts
|

Deeper into divorce: Using actor-partner analyses to explore systemic differences in coparenting conflict following custody dispute resolution.

Abstract: Divorce is an inherently interpersonal experience, yet too often adults' reactions to marital dissolution are investigated as intrapersonal experiences that unfold outside of the relational context in which they exist. This article examines systemic patterns of interpersonal influence between divorced parents who were randomly assigned to either mediate or litigate a child custody dispute in the mid-1980s. Reports of coparenting conflict and nonacceptance of the divorce were assessed 5 weeks after the dispute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 27 publications
2
44
0
4
Order By: Relevance
“…However, both actor and partner attitude familiarity were strongly correlated with conflict and fighting. These data are consistent with work indicating that both members of the dyad appear important for conflict negotiation (Theiss & Knobloch, 2009;Sbarra & Emery, 2008). Although more work is needed, the null partner links with positive interpersonal functioning, especially during social support may reflect the more multiply determined (e.g., Uchino, 2009) or subtle nature of support processes (Bolger, Zuckerman, & Kessler, 2000).…”
Section: Discussionsupporting
confidence: 88%
“…However, both actor and partner attitude familiarity were strongly correlated with conflict and fighting. These data are consistent with work indicating that both members of the dyad appear important for conflict negotiation (Theiss & Knobloch, 2009;Sbarra & Emery, 2008). Although more work is needed, the null partner links with positive interpersonal functioning, especially during social support may reflect the more multiply determined (e.g., Uchino, 2009) or subtle nature of support processes (Bolger, Zuckerman, & Kessler, 2000).…”
Section: Discussionsupporting
confidence: 88%
“…The results indicated that forgiveness, satisfaction with financial child support arrangements, and a low level of hostility during the divorce proceedings predicted cooperation between former spouses. Sbarra and Emery (2008) met with 25 separated-parent dyads who had requested a child custody hearing. These parents were interviewed three times, namely in the first months after dispute resolution and then 1 year and 12 years later.…”
Section: Evolution Of Post-separation Conflictsmentioning
confidence: 99%
“…Sbarra and Hazan (2008) proposed that attachment relationships are defined by the coregulation of felt security within a relationship, and that the loss of felt security associated with romantic separations can result in psychological and physiological dysregulation. In order to cope well with separation distress, people must find a way to soothe themselves (i.e., self-regulate) following the separation experience (Sbarra & Hazan, 2008), and this often involves a reallocation of attentional resources away from an ex-partner and toward other supportive people in one's social network (e.g., Davis, Shaver, & Vernon, 2003; Spielmann, MacDonald, & Wilson, 2009). …”
Section: Attachment Theory and Romantic Separationsmentioning
confidence: 99%
“…The literature on how people cope with and adjust to marital separations has, for the most part, neglected the social context of the separation experience (see Sbarra & Emery, 2008). The end of marriage is a fundamentally social experience—we fight with ex-partners, we discuss how our relationships with them deteriorated, and, if children are involved, we coordinate childcare and celebrate birthdays, holidays, and graduations.…”
Section: The Present Studymentioning
confidence: 99%